High Electricity Generation using Oscillations of Pendulum - Dr. V. Rukkumani; A. Aravindh, P. Balaji; P. Balaji; R. Elumalai; M. Kavin (Journal of Electronic Design Engineering, 2016)
Power generation is one of the major factors in the recent years. To reduce this problem resources like solar energy, wind energy, thermal energy, hydel energy, nuclear energy, etc. have been used. Since with all these above energy resources, we are facing power crisis due to many factors. Future energy sustainability depends heavily on how the renewable energy problem is addressed in the next few decades. The main problems with these energy sources are cost and availability. Wind and solar power are not always available where and when needed. So to avoid these problems renewable energy sources can be used. In this project, the simple pendulum concept is used. The simple pendulum setup with gear mechanism and wiper motor through a PIC microcontroller and relay is employed as it does not require large external energy. The gear mechanism and wiper motor is used along the simple pendulum in order to obtain continuous oscillations where the mechanical energy is converted into electrical energy.